(untitled) (UBS Scientific Bulletin, 2025)
This article is devoted to the issues of connecting the infrastructure of the enclaves and enclaves of the Republic of Uzbekistan with the territory of Uzbekistan. Today, taking into account that these esclaves and enclaves have some difficulties in crossing the borders of neighboring countries, i.e. excessive inspection takes the valuable time of our citizens, it is necessary to take measures to solve this problem between the two countries, ensuring the passage of the railway infrastructure through these areas. it is emphasized that it is necessary to reach a favorable agreement for both parties.